Motivations and barriers for flexitarianism of New Zealand consumers to eating plant-based products : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Food Technology at Massey University, Manawatū, New Zealand - Coetzee, Petra (Massey University, 2022)
Plant-based products (PBPs) are increasingly used by consumers to replace meat in their diet. Different motivators and barriers drive consumers to eat PBPs and ultimately determine whether consumers engage with these foods. Flexitarians, people actively trying to reduce their meat intake, are of particular study interest as they encompass an increasingly larger part of the population than vegetarians and vegans. This study aimed to identify factors that motivate flexitarians in New Zealand to reduce meat intake, and to determine whether age, identified gender and meat consumption frequency play a role. An online questionnaire (n=584) gathered data concerning drivers and barriers to eating meat and PBPs together with demographic information, which was used to further segments flexitarians. Drivers and barriers included demographics, consumption behaviour, ideal sensory characteristics of PBPs, food safety, industry and authority responsibilities, nutrition, health, social status, animal welfare and environment factors associated with consumption of meat and PBPs. Flexitarians with higher meat consumption preferred meat-like properties in ideal PBPs. Generation X (born 1966-80) scored significantly higher than Millennials (born 1981-96) for food safety concerns for pesticides, antibiotics, genetically modified ingredients, and disease. Females scored significantly lower than males for wanting ideal PBPs to bleed-like-meat, be dry and bitter and significantly higher for umami. K-means clustering applied to the motivators and barriers responses identified four flexitarian clusters. Cluster 2 (n = 192) had most motivators for meat reduction whereas cluster 4 (n = 149) had most barriers. Cluster 1 (n = 90) had the lowest food neophobia. Cluster 1 was satisfied with appearance whereas cluster 2 was satisfied with the texture of currently available PBPs. The ideal PBP of clusters 1 and 3 (n = 153) was juicy, savoury, and flavourful. Cluster 2 preferred products to taste like meat. Cluster 3 was similar to cluster 2 in terms of food safety concerns but had higher meat consumption and more barriers to PBP consumption. Flexitarian segments differed in the drivers and barriers to eating meat and PBPs, suggesting they engage differently with PBPs. Future studies should investigate this difference including sensory evaluation of PBPs. These results can aid industry in developing and promoting products that meet clusters’ needs.
Keywords: 300602 Food chemistry and food sensory science